LEGAL CONSEQUENCES OF REDUCED INDEPENDENCE OF SUBSIDIARIES BY PARENT CONTROL IN HOLDING COMPANY (STUDY ON PLANTATION SOE HOLDING) - Sebayang, Supriyadi (Inspiring Law Journal, 2024)
PT Perkebunan Nusantara III (Persero) is the holding company for PT Perkebunan Nusantara I, II, IV to XIV in the Perkebunan BUMN Holding structure. In order to accelerate the operations of the Plantation BUMN Holding, the parent company exercises control by issuing a set of policy norms to be applied to subsidiaries. However, in practice, apart from issuing policy provisions, the parent company is also directly involved in the operations of the subsidiary down to the most technical matters, so that the subsidiary as a separate legal entity that is separate from its owner (Shareholders) has lost its independence in managing the operations of the subsidiary as it should be. implemented by the Subsidiary's Directors. The most crucial problem that arises in this research is whether the legal consequences for the parent company's control cause the subsidiary to lose its independence. The theories used in this research are the theory of Corporate Legal Entity and Piercing the Corporate Veil. The results of this research conclude that juridically, the legal status of the parent company and subsidiary companies is that they are independent legal entities and each has the right to carry out its own legal actions. However, in business reality it cannot be denied that subsidiary operations are completely under the control of the parent holding company. In this case the subsidiary has become the alter ego for the Shareholders (PTPN III). Thus referring to the doctrine of piercing the corporate veil, Shareholders (PTPN III) have the potential to be held responsible for personal assets (PTPN III) if losses occur to the company and third parties